The role of rural banks in credit creation and poverty reduction in Ghana: a case study of Nwabiagya Rural Bank, Ashanti region - Appiah-Kubi, Ebenezer (2011)
A thesis submitted to the Department of Banking and finance, Kwame Nkrumah University of Science and Technology of Master of Executive Business Administration, KNUST School of Business.